The Integration between the Target Cost and Product Lifecycle in Achieving Advantage - Abd, Nuha Safi; Jasim, Asmaa Noaman (Opción, 2019)
The research aims to measure the cost of production of the grains of Aspin for children in the grain production department of the state company for drugs industry and medical appliances via the descriptive approach through the case study method. The search has yielded many results. The most prominent of these results, cost management tools (Target Cost) support the product lifecycle, and the product lifecycle supports target cost. In conclusion, developments in modern accounting methods have had a significant impact on achieving the competitive advantage of companies, resulting in the need for cost management tools.